Reprint of: The effect of the Music Day event on community drug use. (September 2020) - Devault, Damien A.; Peyré, Alexandre; Jaupitre, Olivier; Daveluy, Amélie; Karolak, Sara
Highlights: Illicit drug consumption has been monitored during Music Days. Non-peered audience reduces the affinity drug consumption in festival. Alcohol consumption is an alternative to illicit drug in public. Abstract: Illicit drugs consumption can be back-calculated based on the analysis of drug residues in wastewater using the wastewater-based epidemiology method. The Music Day, held on June 21 in France since 1982, has grown to global proportions and is now celebrated as World Music Day. This large outdoor event takes place in many cities with people allowed to play music in the streets. As psychotropic drugs are often associated with music events, the goal of this study is to investigate the use of illicit drugs on this day in Bordeaux, the fifth largest urban area in France. Daily sampling campaigns of composite wastewater were carried out for seven days in two wastewater treatment plants in Bordeaux in 2017 (Music Day) and 2018. World Music Day in Bordeaux has no observable effect on illicit drug consumption even if this event has massive public participation: this is the first report of the absence of an illicit drug consumption increase in a festival of such magnitude, corroborating the effect of others' views and opinions, because this event takes place publicly in the street and not among peers. Different hypothesizes are put forward to explain this fact: inappropriate type of event for drug consumption, effect of other festivals, and influence of the event's timing on a weekday.